Effect of Music on Reducing Anxiety for Patients Undergoing Transrectal Ultrasound-Guided Prostate Biopsies: Randomized Prospective Trial - Cho, Seong Whi; Choi, Hyuck Jae (Urology Journal, 2016)
Purpose: The purpose of this study was to assess the impact of music on anxiety and perceived pain during transrectal ultrasound-guided prostate biopsy. Materials and Methods: Forty consecutive men with an elevated serum prostate specific antigen (PSA) level and/ or an abnormal digital rectal examination referred for transrectal ultrasound-guided prostate biopsy were recruited and allocated to a music (n = 20) or a non-music (n = 20) group. Anxiety was assessed prior to and after biopsy and pain was assessed after biopsy in each patient using visual analog scales (VAS) in the same setting, and group anxiety scores were compared. Results: Patients in the music group experienced less anxiety (P = .046) during the procedure, but group pain scores were not significantly different. Conclusion: Music was found to decrease anxiety effectively during transrectal ultrasound-guided prostate biopsy.